COMPOSITION, STRUCTURE, CORRELATION AND LOCAL WISDOM OF ULIN (Eusideroxylon zwageri Teijsm. & Binn.) IN TAU LUMBIS- NORT BORNEO - asep sadili (Pusbindiklat - LIPI, 2019)
The species of iron wood or locally known as ulin/tahas, is recognized as strong and durable. This study aims to provide information about condition and corelation of iron woods in natural forests of Tau Lumbis area, including its utilization and conservation through local knowledge of Dayak Akolod and Tagol tribes. The study was conducted in natural forests in Kabungolor and Kabalob (North Kalimantan). It used a plot and selected ulin tree as the midpoint of the plot. Each trees with diameter > 10 cm in the plot were measured for its stem circumference at ±1.3 m from the ground. There were 13 individuals/ha of ulin trees in Kabalob plot and 25 individuals/ha of ulin trees in Kabungolor plot (an average of ±19 individuals/ha). Based on the density measurements, there were no correlation between ulin tree and other trees species in the two locations. The iron woods were used for various needs from generation to generation by the Dayak Akolod and DTagol tribes without paying much of attention to its conservation.